A MINI-REVIEW OF ELECTROANALYTICAL METHODS FOR PESTICIDES QUANTIFICATION - Jevtić, Sonja; Stanković, Dalibor; Jokić, Anja; Petković, Branka (Bulletin of Natural Sciences Research, 2019)
This review paper shows the progress made in the last five years in electrochemical methods applied for the purpose of detection and quantification of pesticides - nowadays the most serious pollutants of the environment. Most pesticides can be successfully analyzed by chromatographic techniques, but because of high prices and immobility of the apparatus, the complexity of the method and the necessary special preparation of the samples, electrochemical methods have been recognized as an excellent alternative solution due to their advantages in speed, economy, simplicity and no exhaustive sample preparation. As the main limitation for use of this methods is electrochemical inactivity of many pesticides, this paper gives the essence of all elctroanalytical methods for pesticide quantification applied in last period, with an overview of the electrode materials and modifiers applied in a purpose to enhance analytical procedures application and characteristics of electrochemical sensors.